Lake eutrophication management assessing and controlling the limiting nutrient through integrated lake watershed and water quality model in Laguna lake Philippines (west bay area) - Winastu, Hendra (2012)
Laguna Lake is one of the important inland waters of the Philippines. The nutrient loading that leads to eutrophication is one of the main issues for Laguna Lake water quality management. Historical trend shows that trophic condition in West Bay area varies from mesotrophic to hyper-eutrophic. Trophic condition is dominated by transition state from eutrophic to hyper-eutrophic regardless of the seasonal changes that occur within the lake. Limiting nutrient scheme also varies but in the recent condition toward hyper-eutrophic phosphorous have been determined to be the limiting nutrient. Physical-biochemical processes highlighted from measured parameters such as TS, TDS, chloride, total hardness, DO, temperature, calcium hardness, BOD, COD, turbidity, light intensity and chlorophyll-a have high variance in correlation with lake eutrophication. The estimated nutrient loading for Calabarzon region shows that livestock rising is the main source of nutrient enrichment compared with domestic and agricultural activities. Nitrogen content is 10 times higher than phosphorous in the overall estimated nutrient loading. The more recent data o nutrient enrichment through watershed simulation between 2006-2009 shows that increasing trend of nutrient realtively matches with trophic variation toward hyper-eutrophic condition especially in the West Bay area. Combination of topography, land use, soil cover and rainfall are the main factors that affect nutrient enrichment from the lake watershed. However, predicted total phosphorous from fish feeding practice shows no significant contribution on nutrient enrichment into Laguna Lake. Critical water quality parameters for fishery seem to be advantageous for aquaculture activity in Laguna Lake. Inorganic phosphorous within lake-bottom sediment that is three times higher than organic phosphorous highlights the possible nutrient storage on lake-bottom sediment that might involve in effective nutrient cycle within the lake through internal nutrient loading scenario. Water quality simulation outputs in 2009 suggest that biological productivity cold adjust with minimum nitrogen source as well as possibility of optimum phosphorous uptake. nitrogen source control seems to be effective based on this 2009 simulation scheme. Simulation output of aquaculture practice also confirms that there is no significant contribution on feeding scheme to promote biological productivity.